Using PLFA to constrain microbial distribution related to S-cycling in oil-sands composite tailings during reclamation - Ngonadi, Nwaneoma (My University, 2013)
Microorganisms are the most abundant living things on the planet and they drive many important environmental processes. They can do this by coupling reduction – oxidation (redox) reactions. In such reactions, the oxidation of reduced organic matter is coupled with the reduction of another compound, which serves as the electron acceptor. All microbes contain lipids in their cells; phospholipids are the main components of the cell membrane where they make up a consistent component of cell mass. Therefore, in situations where direct cell count is unrealistic, lipid analysis can be used to provide information on microbial communities. Because they hydrolyze shortly after cell death,PLFAs indicate only viable cell biomass, and PLFA analysis provides valuable insight on cell density distribution across a site. One application of PLFA analysis is within this thesis, where it was used to investigate the microbial community at Mildred Lake, Syncrude’s primary tailings settling basin. At Mildred Lake, Syncrude is constructing a freshwater fen over the deposited composite tailings (CT) as part of their reclamation process. Understanding the microbial biogeochemical cycling associated with these reclamation activities is an important component for management decisions affecting the site and thus, inform future reclamation activities.
PLFA analysis on samples from the site showed variable concentrations equivalent to estimated cell densities on the order of 107 decreasing to 106 in the CT.These cell density ranges are expected for oligotrophic systems. Phospholipids can also be biomarkers if they are indicative of a specific group of microbes. The study at Mildred Lake identified biomarkers for sulfate reducing bacteria (SRBs). The presence of these biomarkers provided a basis for the hypothesis that sulfide detected at the site was potentially from SRBs.
This thesis provides information on the fundamental concepts of lipids and the application of lipid analysis on the environmental samples from the Mildred Lake site to understand its microbial community and cycling of sulfur to prevent potential environmental issues associated with the generation of sulfide.
Keywords: oil sands; plfa; hydrogen sulfide; cell density; syncrude; Geochemistry; Geochemistry